2012
DOI: 10.2165/11632780-000000000-00000
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Clinical Pharmacokinetics of Nemonoxacin, a Novel Non-Fluorinated Quinolone, in Healthy Chinese Volunteers Following Single and Multiple Oral Doses

Abstract: Nemonoxacin exhibited a linear PK profile in the 250-750 mg dose range with moderate food effects. There was no accumulation following consecutive administration for 10 days. The PK and safety profiles of nemonoxacin in Chinese subjects support evaluation of once-daily dosing in the future development of this agent.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
57
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 18 publications
0
57
0
Order By: Relevance
“…(Ae 0 -72 h after administration of 250 to 750 mg reported as 66.00% to 70.28% [7]) and higher than values obtained from a North American study in which subjects received a single dose of between 25 mg and 1,500 mg of nemonoxacin (Ae 0 -72 h , 34.15% to 56.24%). C max values following i.v.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…(Ae 0 -72 h after administration of 250 to 750 mg reported as 66.00% to 70.28% [7]) and higher than values obtained from a North American study in which subjects received a single dose of between 25 mg and 1,500 mg of nemonoxacin (Ae 0 -72 h , 34.15% to 56.24%). C max values following i.v.…”
Section: Discussionmentioning
confidence: 67%
“…Oral administration of 500 mg or 750 mg nemonoxacin once daily for 10 days is well tolerated in healthy subjects (7). The phase II and III clinical studies also demonstrated that the clinical and microbiological efficacies of oral nemonoxacin (500 mg daily for 7 to 10 days) were comparable to those of oral levofloxacin (500 mg daily) for the treatment of mild to moderate community-acquired pneumonia (CAP).…”
mentioning
confidence: 99%
“…The profile of intravenous nemonoxacin had characteristics similar to those of the nemonoxacin capsule in healthy volunteers (13). For example, the C max of i.v.…”
Section: Discussionmentioning
confidence: 75%
“…The half-life (t 1/2 ) of nemonoxacin in the capsule formulation was about 11 h, and about 70% of the administered dose was excreted by the kidneys in an unchanged form. The two oral regimens, 500 mg or 750 mg once daily for 10 consecutive days under fasting conditions, were also well tolerated in Chinese subjects (13).…”
mentioning
confidence: 99%
“…Oral nemonoxacin, 750 mg and 500 mg given once daily for 7 days, showed high biological success rates for common bacterial pathogens and high clinical success rates for atypical pathogens of community-acquired pneumonia. Nemonoxacin was well tolerated, and no serious drug-related adverse events were observed (12,13).…”
mentioning
confidence: 93%